UV-MALDI Mass Spectrometry Analysis of NBD-Glycosphingolipids Without an External Matrix - Landoni, M. (2008)
Each day, advances in the instrumentation and operating protocols bring new applications and insights into the molecular processes of ultra violet-matrix assisted laser desorption/ionization-mass spectrometry (UV-MALDI MS), increasing its potential use. We report here an approach in which mass spectrometry analysis of sphingolipids has been performed using a fluorescent tag (nitrobenz-2-oxa-1, 3-diazole, NBD) covalently linked to the sphingoid base as matrix. Thus, different labeled-sphingolipids were analyzed: ceramide, dihydroceramide, acetylceramide, glucosylceramide, galactosylceramide, galactosyldihydroceramide. In addition an extract of glycosphingolipids obtained from epimastigote forms of Trypanosoma cruzi metabolically labeled with NBD-ceramide was analyzed. The goal of this work is to show that no matrix needs to be added for the mass spectrometry analysis as the same tag used to label the lipids may generate efficiently analyte ions to obtain high quality signals. © 2008 American Society for Mass Spectrometry.